Clinical and epidemiological characteristics of nutritional status in recently admitted students of a private medical school - Riveros-Chavez, Stephany (2020)
Objectives: to determine the frequency of malnutrition in students recently admitted to a private medical school in 2018. Materials and methods: this is a cross-sectional and retrospective study which consisted in reviewing the records from students admitted in 2018 to a private medical school in Lima, Peru. Absolute and relative rates were obtained, Chi-square test and Fisher’s exact test were used for qualitative variables and U Mann-Whitney’s test or Student’s t test were used for quantitative variables. Significance level was set at 95%. Results: the study population consisted of 263 subjects. More than half of them (53.99%) had malnutrition, which was established as 36.5% overweight persons, 11.03% were obese, and 6.46% were undernourished. The following findings were associated to malnutrition: alcohol consumption (p<0.001), family history of type 2 diabetes (p<0.001), district of origin (p= 0.014), and abdominal circumference (p<0.001). Conclusions: more than half of the students admitted to a private medical school had malnutrition, mainly because of being overweight, and this was associated with cardiovascular risk because of having large abdominal circumference and altered laboratory tests. Variables associated to malnutrition were as follows: alcohol consumption, tobacco use, family history of type 2 diabetes, district of origin, and abdominal circumference.